A Line Objects Recognition Algorithm based on Non-subsampled Contourlet Transform - Jiang, Qinghua; Yang, Yi; Zhang, Meng; Zhang, Sixian (Chinese Control Conference, 2020)
Aiming at the recognition of line features represented by bridges and airport runways in remote sensing data, this paper presents a line objects extraction algorithm based on Non-subsampled Contourlet Transform(NSCT). Firstly, NSCT is used to decompose the source image into multiple layers and directions to obtain the corresponding frequency sub-bands. Then the Line Segment Detection(LSD) algorithm with visual saliency is used to detect the line segments. Finally, line objects recognition is completed by multi-scale and multi-direction line features combination according to the established fusion rules. Comparison with some traditional algorithms verifies that the proposed algorithm can improve the recognition accuracy.